Identification of design related distortion of gear base bodies by finite element computations: Identifikation der konstruktiv bedingten Maß‐ und Formänderungen von Zahnradgrundkörpern mittels Finite‐Element‐Methode. Issue 8 (4th August 2016) - Surm, H.; Hunkel, M.; Lübben, T.
Abstract : The effect of design related distortion of gear base bodies was investigated by finite element analysis. Local size and shape alterations due to a case hardening process were compared with corresponding experimental results. Possible reasons for the deviations between experiment and calculation were identified by exemplary sensitivity analysis of material and process parameters. Future measures were discussed for improvement of the calculation results. According to the current level of computation the identification of design related distortion of gear base bodies by finite element analysis is associated with a certain degree of uncertainty.